Water Management Challenges in Coastal Polders of Bangladesh: Adaptation Planning Through Climate-Smart Mapping — An Innovation - Amin, Md. Ruhul; Salahuddin, Ahmad (International Rice Research Institute, 2025)
The coastal polders of Bangladesh, form a unique hydrological landscape essential for agricultural production, water regulation, and climate resilience. Despite extensive embankments, sluice gates, and canals, water management in these polders faces mounting challenges from climate risks, weak infrastructure maintenance, fragmented institutional mandates, and limited community participation. This policy brief synthesizes findings from two studies: (1) institutional challenges in polder water management, and (2) Climate-Smart Mapping and Adaptation Planning (CS-MAP) conducted across 10 coastal districts. Results show that water management-related issues account for over half of community-identified adaptation needs. CS-MAP emerges as a robust, participatory, evidence-based planning tool that can guide targeted interventions such as improving drainage systems, enhancing sluice gate operation, excavating canals and ponds, and promoting climate-resilient crop varieties. To build climate-smart, inclusive, and sustainable polder systems, the brief recommends strengthening Water Management Organizations (WMOs), designating a lead agency for community-centered water governance, realigning institutional mandates, reforming existing policies, and integrating CS-MAP into formal planning processes. A shift toward integrated and participatory water governance is essential for enhancing agricultural resilience and ensuring long-term sustainability in Bangladesh’s coastal polders.